2013
DOI: 10.1073/pnas.1215626110
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of excess risk for diabetes for those born in times of hunger, in an entire population of a nation, across a century

Abstract: Based on a unique dataset comprising all 325,000 Austrian patients that were under pharmaceutical treatment for diabetes during 2006 and 2007, we measured the excess risk of developing diabetes triggered by undernourishment in early life. We studied the percentage of all diabetes patients in the total population specifically for each year of birth, from 1917 to 2007. We found a massive excess risk of diabetes in people born during the times of the three major famines and immediately after, which occurred in Au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
85
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(91 citation statements)
references
References 38 publications
3
85
1
1
Order By: Relevance
“…The dawn of big-data science offers a novel and intriguing way to address this concern. For example, a recent study investigated the relation between early childhood exposure to famines and the risk of developing diabetes using a nationwide dataset of all Austrian outpatient claims over 2 years [29]. With a population of 8.3 million people containing 325,000 diabetes patients, this study reflects an increase in cohort size of more than a factor of 1,000 when compared to the natural experiments discussed above.…”
Section: Epidemiological Evidence and Natural Experimentsmentioning
confidence: 92%
See 1 more Smart Citation
“…The dawn of big-data science offers a novel and intriguing way to address this concern. For example, a recent study investigated the relation between early childhood exposure to famines and the risk of developing diabetes using a nationwide dataset of all Austrian outpatient claims over 2 years [29]. With a population of 8.3 million people containing 325,000 diabetes patients, this study reflects an increase in cohort size of more than a factor of 1,000 when compared to the natural experiments discussed above.…”
Section: Epidemiological Evidence and Natural Experimentsmentioning
confidence: 92%
“…Economic crisis, massive unemployment, and bad harvests led to a famine in many places in early 1938. Finally, in the wake of World War II a third period of hunger occurred in 1946/1947 with a reported average food intake between 500 and 800 calories [29]. …”
Section: Epidemiological Evidence and Natural Experimentsmentioning
confidence: 99%
“…However, it seems like these effects can be stable even when the initiating stimulus is removed and affect the probability that the individual will develop diseases like obesity and type 2 diabetes later in its adult life. The correlation between transgenerational and in-utero/early life experiences with the risk of disease in adulthood is extensively studied both epidemiologically [146][147][148][149][150][151] and at the level of modifications in animal models [152,153] as well as in humans [154][155][156]. The number of reviews on the topic of linking epigenetic modifications to obesity and T2D seems convincingly huge, e.g.…”
Section: Histones In Human Adipocytesmentioning
confidence: 99%
“…Most striking were the results of a recent total population study that revealed massively increased risk for diabetes mellitus in those born during and immediately after 3 major famines in Austria over the last century. 184 The timespan between intrauterine development and adult disease onset limits the direct evidence of epigenetic mechanisms underlying maternal nutrient programming of metabolic function in humans. Furthermore, the relative contributions of genetic and environmental factors to the developing human epigenome are difficult to distinguish in outbred populations.…”
Section: Undernutrition In Uteromentioning
confidence: 99%
“…242 More recently, germ cell DNA hypomethylation was associated with the transmission of metabolic dysfunction from diet-induced obese paternal mice to 2 subsequent generations. 243 Identification of gestationally determined epigenetic changes associated with metabolic disease in humans provides potential mechanisms to explain disease risk in many historical famine cohorts 184,244 and is equally relevant to recent and current famines around the globe. The effects of longterm poverty on changes in body shape 245 are likely to include nutritional-epigenetic components.…”
Section: Epigenome and Public Healthmentioning
confidence: 99%